2020
DOI: 10.3390/jcm9041241
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab for the Treatment of Atopic Dermatitis in an Austrian Cohort-Real-Life Data Shows Rosacea-Like Folliculitis

Abstract: Dupilumab is the first biological treatment approved for moderate-to-severe atopic dermatitis (AD). Efficacy and safety have been demonstrated in clinical trials, but real-life data is still limited. The objective of this study was to retrospectively evaluate Dupilumab treatment in AD patients in a real-life clinical setting. Effectiveness and safety outcomes were collected at baseline and after 2, 6, 10, 24, 39, and 52 weeks by using clinical scores for disease activity, as well as serological markers. Ninety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…Mechanisms that restrain the fecundity, growth and/or maintenance of follicular mites are little studied, and the models we describe will be useful to probe these pathways as well as implications for disease in the colonized host, such as tolerance to allergens or proclivity to AD. Of note, patients treated with anti-IL4Ra antagonist for atopic dermatitis have increased incidence of conjunctivitis associated with demidocosis 35 , suggesting pathways we uncover here likely participate in control of follicular mites in humans.…”
Section: Discussionmentioning
confidence: 82%
“…Several retrospective real‐life cohorts and AD registries report similar impact of dupilumab on AD severity as in RCTs with an acceptable safety profile 83,85,86,149,150 …”
Section: Discussionmentioning
confidence: 92%